OsLFR is essential for early endosperm and embryo development by interacting with SWI/SNF complex members in Oryza sativa. (7th September 2020) - Qi, Dongmei; Wen, Qingqing; Meng, Ze; Yuan, Shan; Guo, Hong; Zhao, Hongtao; Cui, Sujuan
SUMMARY: Rice ( Oryza sativa L .) endosperm provides the developing embryo with nutrients and provides human beings with a staple food. The embryo eventually develops into a new sporophyte generation. Despite their important roles, the molecular mechanisms underlying early‐stage endosperm and embryo development remain elusive. Here, we established the fundamental functions of rice OsLFR, an ortholog of the Arabidopsis SWI/SNF chromatin‐remodeling complex (CRC) component LFR. OsLFR was expressed primarily in the rice spikelets and seeds, and the OsLFR protein was localized to the nucleus. We conducted genetic, cellular and molecular analyses of loss‐of‐function mutants and transgenic rescue lines. OsLFR depletion resulted in homozygous lethality in the early seed stage through endosperm and embryo defects, which could be successfully recovered by the OsLFR genomic sequence. Cytological observations revealed that the oslfr endosperm had relatively fewer free nuclei, had abnormal and arrested cellularization, and demonstrated premature programed cell death: the embryo was reduced in size and failed to differentiate. Transcriptome profiling showed that many genes, involved in DNA replication, cell cycle, cell wall assembly and cell death, were differentially expressed in a knockout mutant of OsLFR ( oslfr ‐1 ), which was consistent with the observed seed defects. Protein–protein interaction analysis showed that OsLFR physically interacts with several putative rice SWI/SNF CRC components. Our findings demonstrate that OsLFR, possibly as one component of the SWI/SNF CRC, is an essential regulator of rice seed development, and provide further insights into the regulatory mechanism of early‐stage rice endosperm and embryo development. Significance Statement: We disclose that OsLFR, a rice ortholog of the Arabidopsis SWI/SNF component LFR, is essential for free nuclei division, endosperm cellularization and embryo differentiation. Thus, one functional role of the OsLFR gene in the early stage of rice endosperm and embryo development is revealed.